NEWS APPROACH FROM THE DIGITAL PRESS OF SPAIN ON ISLAM - Mora Vega, Roy (2020)
The article analyzes the news approach used by three Spanish media, in its digital edition, during 2016 when addressing news related to Islam and Muslim communities, to determine how these approaches contribute to the construction of collective discourses and imagery that affect these human groups. The study used deductive logic, and content analysis as a research method. The most recurring keywords and themes were identified in the news articles, as well as a relationship between this content with the categories of "Islamophobia" and "hate speech". It is concluded that the approaches used by the media contribute to the creation of Islamophobic visions and hate speech towards the studied communities.